The prognostic value of the systemic immune-inflammation index for patients with bladder cancer after radical cystectomy - Zhang, Shiyu; Du, Jiajia; Zhong, Xin; Tan, Ping; Xu, Hang; Zhang, Jiapeng; Jin, Di; Li, Yifan; Le, Weizhen; Xiong, Xingyu; Lin, Tianhai; Wei, Qiang (Frontiers in Immunology, 2022)
Background Biomarkers acquired from blood samples are easy to obtain and cost-effective, have attracted considerable interest, and have been widely investigated. Inflammation plays a crucial role in cancer cell initiation, proliferation, and metastasis. We aimed to evaluate the association of the preoperative systemic immune-inflammation index (SII) with the clinical outcomes of patients diagnosed with bladder cancer and who underwent radical cystectomy (RC). Materials and methods Data from patients diagnosed with bladder cancer and who underwent RC from December 2010 to May 2020 in West China Hospital were retrospectively collected according to the inclusion and exclusion criteria. Patients were divided into a low-SII group and a high-SII group according to the SII level. Survival outcomes were obtained during follow-up. The primary endpoints were overall survival (OS) and recurrence-free survival (RFS). Cox proportional hazard models were performed to estimate the effect of SII on OS and RFS and control for potential confoundings. Subgroup analyses were conducted, and the log likelihood ratio test was used to inspect the interaction. Results A total of 725 patients who underwent RC were ultimately involved in this study. Of these patients, 621 (85.66%) were men and 104 (14.34%) were women. The median age was 65 years. The median follow-up was 36 months for OS and 33.6 months for RFS. The optimal cutoff value was identified as 554.23 × 109/l. A total of 467 (64.41%) patients were divided into the low-SII group (SII <554 × 109/l), and 258 (35.59%) patients were divided into the high-SII group (SII ≥554 × 109/l) accordingly. Multivariable Cox proportional hazard regression demonstrated that a high SII was an independent prognostic factor for worse OS (HR: 1.69 95% CI: 1.02–2.81, P = 0.0436) and RFS (HR: 1.88, 95% CI: 1.09–3.24, P = 0.0229) in NMIBC patients. A high SII was found to be an independent prognostic factor for worse RFS in patients with HBP (HR: 2.11, 95% CI: 1.34–3.30, P = 0.0012), with DM (HR: 3.76, 95% CI: 1.73–8.15, P = 0.0008), and without PNI (HR: 1.32, 95% CI: 1.04–1.69, P = 0.0238). Conclusions The SII was a potential prognostic predictor for bladder cancer patients who underwent RC. Further prospective multicenter investigations are warranted.